Effect of Motivation and Satisfaction on Performance with Discipline as Mediator - Sibarani, Dina Damaris; Okta , Hafrizal; Nurlina, Nurlina (Research Horizon, 2025)
Employee performance is a critical factor in organizational success and is influenced by various psychological and behavioral factors. Among them, work motivation and job satisfaction play significant roles in shaping employee behavior and outcomes. However, the role of work discipline as an intervening variable in this relationship has not been thoroughly explored, especially in cooperative institutions. This study aims to identify and analyze the influence of work motivation and job satisfaction on employee performance, with work discipline serving as a mediating variable.  This research uses a quantitative approach, involving 128 employees selected through probability sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling. The results indicate that neither work motivation (P = 0.426) nor job satisfaction (P = 0.112) has a direct, significant effect on work discipline. Likewise, neither work motivation (P = 0.154) nor job satisfaction (P = 0.112) has a direct influence on employee performance. However, work discipline has a significant impact on performance (P = 0.187), and it mediates the effect of work motivation (P = 0.010) and job satisfaction (P = 0.002) on employee performance. Work discipline plays a crucial mediating role in translating motivation and satisfaction into improved employee performance.